A new species in the water mite subgenus Majumderatax Vidrine, 1993 from Sri Lanka (Acari: Hydrachnidia) - Pešić, Vladimir; Zawal, Andrzej (Zootaxa, 2018)
Majumderatax was originally established by Vidrine (1993) as a subgenus of Unionicola Haldeman, 1842 with U. hankoi Szalay, 1927 as type species. It is probably a monophyletic clade (Gerecke et al. 2016), characterized by the following features: (i) I-L-5 with a characteristic, blade-like distoventral seta, and (ii) P-5 short and stocky, with a strong, bifurcated claw.